Nano-impact voltammetry - Bartlett, T (2017)
This thesis introduces new concepts to the study of nanoparticles by nano-impact voltammetry. Utilising the special chemistries of metal halide and metal oxide nanoparticles, the use of the nano-impact technique is expanded beyond quantitative sizing towards the study of the in-situ synthesis and detection of nanoparticles, reversible agglomeration behaviour and the fabrication of nanoelectrode arrays. Nano-impact voltammetry is also demonstrated to be an informative tool for the tracking of chemical and photochemical conversion reactions of metal halide nanoparticles and for the mechanistic determination of metallic nanoparticle growth during synthesis. The use of forced convection to gain improvements in the detection limit achievable for the direct-impact of metallic nanoparticles is also reported. Initially, the work reported herein looks at the direct-impact voltammetry of previously unstudied nanomaterials; mercury(I) chloride, silver bromide and bismuth oxide. The first sizing of metal halide nanoparticles is reported as well as a method for synthesising particles through the electrolytic induced implosion of a nanoscale metal halide layer on a liquid electrode. The "upper-limit" of the nano-impact technique is also quantified through the use of silver bromide and silver nanoparticles with diameters approaching 100 nm successfully studied. Next, bismuth oxide nanoparticles are studied by the nano-impact method to probe the reversible agglomeration of particles. By reducing impacting bismuth oxide nanoparticles at the electrode, bismuth deposits are shown to result and can be imaged by scanning electron microscopy. Through the analysis of these deposits, in combination with nanoparticle tracking analysis, experimental evidence for the voltammetrically induced de-agglomeration of nanoparticles is proposed. In the subsequent chapter, nano-impact voltammetry is employed in the study of photochemical reactions. First, the photochemical reduction of silver bromide nanoparticles to silver nanoparticles is followed both by ultra-violet visible spectroscopy and nano-impacts, allowing mechanistic determination of the conversion process. Second, the nano-impact technique is used in combination with ultra-violet visible spectroscopy and transmission electron microscopy for the mechanistic determination of the photochemical Ostwald ripening of silver nanoprisms from silver nanoseeds. Finally, the inter-play between nano-impacts and electrode arrays is reported. Through the electrolysis of impacting silver bromide nanoparticles, it is shown that a functional silver nanoelectrode array can be formed. The formed nanoelectrode array is characterised by the electrocatalytic reduction of hydrogen peroxide. The lowest reported detection limit for silver nanoparticles is also reported, through the combination of a random array of microelectrodes and a specially developed, custom built, and characterised wall-jet flow cell.